Effectiveness of psychosocial interventions in reducing grief experienced by family carers of people with dementia: a systematic review. - Wilson, S.; Toye, Christine; Aoun, S.; Slatyer, S.; Moyle, W.; Beattie, E. (The University of Adelaide, 2017)
Background: Family carers of people living and dying with dementia experience grief. The prevalence, predictors and associated factors of grief in this population have been identified, and psychosocial interventions to decrease grief symptoms have been implemented. However, the effect of psychosocial interventions on family carers’ grief, loss or bereavement has not been examined. Objective: To synthesize the existing evidence regarding the impact of psychosocial interventions to assist adjustment to grief, pre- and post-bereavement, for family carers of people with dementia. Inclusion criteria Types of participants: Family carers of older persons with dementia (> 65 years). Types of interventions: Psychosocial interventions in health and social care facilities, and community settings designed to assist family carers adjust to grief during the dementia trajectory and/or following death. Comparisons: No treatment, standard care or treatment as usual, or an alternative intervention. Types of studies: Experimental and epidemiological study designs. Outcomes: Grief in family carers including anticipatory, complicated and prolonged grief disorder measured with validated instruments. Search strategy: A three-step strategy sought to identify both published and unpublished studies from 1995. Methodological quality: Assessed by two independent reviewers using standardized critical appraisal tools from the Joanna Briggs Institute Meta Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI). Data extraction: The standardized data extraction tool from JBI-MAStARI was used by two reviewers independently. Data synthesi:s Statistical pooling of results was not possible due to the heterogeneity of the interventions and the outcome measures. Results: Data were extracted from three studies. Study designs were a randomized controlled trial; a pre-test, multiple post-test quasi-experimental; and a single group, repeated measures. The interventions were multi-component, had durations of nine to 26 weeks and were delivered while care recipients were alive. All studies were undertaken in the United States. There were 327 family carers, of which 197 received a psychosocial intervention. Family carers were predominantly female (84.7%), Caucasian (73.4%) and caring for their spouse (44.3%). All care recipients had dementia; 68.5% had Alzheimer's disease. Two studies measured anticipatory grief, and the third study reported normal and complicated grief. Moderate benefits to anticipatory grief were evident upon completion of the “Easing the Way” intervention (effect size −0.43, P = 0.03). After controlling for research design and control variables, for every hour increase in the interventions focusing on family carers’ cognitive skills, there were associated decreases in carers’ normal grief (parameter estimate [PE] = −0.81, P = 0.02) and complicated grief (PE = −0.87, P = 0.03). For every hour increase in the interventions focusing on carer behavior, there was an associated decrease in carers’ complicated grief (PE = −1.32, P = 0.04). For every hour increase in the interventions focusing on care recipient behavior, there was an associated decrease in carers’ complicated grief (PE = −2.91, P = 0.04). Conclusion: There is little evidence upon which to base practice with regard to interventions to reduce any aspects of grief. Findings suggest that different pre-death interventions might be warranted depending upon a family carer's unique clinical presentation and combination of risk factors. Cognitive skills training provided while the care recipient is alive may positively impact normal and complicated grief following the death of the care recipient. When the cognitive skills training is provided in conjunction with behaviorally oriented interventions that improve the wellbeing of the carer and care recipient, carers’ complicated grief symptoms may be reduced.